An elderly lady with dementia and myoclonus : Think of Sporadic Creutzfeldt Jakob Disease (Bangladesh Critical Care Journal, 2018)
Creutzfeldt Jakob disease (CJD) is an incurable, invariably fatal, rapidly progressive neurodegenerative disease caused by an abnormal isoform of a cellular glycoprotein known as the prion protein. CJD occurs worldwide, estimated annual incidence is about one case per million populations per year. Sporadic Creutzfeldt Jakob disease (sCJD) is a human prion disease; infection with this disease usually leads to death within one year of onset of illness. The characteristic clinical & diagnostic features of rapidly progressive dementia, myoclonus, visual or cerebellar signs, pyramidal/extrapyramidal sign, Akinetic mutism and positive result on the presence of 14-3-3 protein in CSF assay, typical EEG features and MRI findings of brain are highly suggestive of diagnosis. Biopsy of brain for histopathological examination is more specific & confirmatory for diagnosis. This article reports a case of sCJD who was diagnosed by characteristic findings of MRI of brain, Electroencephalography (EEG) & cerebrospinal (CSF) assay at National University Hospital (NUH), Singapore and later on admitted at United Hospital Limited (UHL) Dhaka for palliative and supportive management.Bangladesh Crit Care J September 2018; 6(2): 100-101